TO STUDY THE CONSUMER PERCEPTIONS TOWARDS BUILDING SELF-MOTIVATION THROUGH VARIOUS ONLINE MARKETING STRATEGIES (Global Journal of Advanced Engineering Technologies and Sciences, 2017)
Marketers have long understood that consumers' self-concepts influence the products they purchase; conversely, products purchased influence people's self-concepts. Using the symbolic interactionist perspective of identity theory, this study empirically tests the proposition thatonline consumers use electronic word of mouth, and specifically the sharing of online advertising, to construct and express their self-concepts. The results suggest that self-brand congruity, entertainment value, and product category involvement increase theself-expressiveness of online ads, which then increase the likelihood of sharing those ads. These findings have both theoretical and managerial implications.